Fatty Acid Trafficking Between Lipid Droplets and Mitochondria: An Emerging Perspective - Smolková, Katarína; Gotvaldová, Klára (International journal of biological sciences, 2025)
The current understanding of lipid droplets (LDs) in cell biology has evolved from being viewed merely as storage compartments. LDs are now recognized as metabolic hubs that act as cytosolic buffers against the detrimental effects of free fatty acids (FAs). Upon activation, FAs traverse various cellular pathways, including oxidation in mitochondria, integration into complex lipids, or storage in triacylglycerols (TGs). Maintaining a balance among these processes is crucial in cellular FA trafficking, and under metabolically challenging circumstances the routes of FA metabolism adapt to meet the current cellular needs. This typically involves an increased demand for anabolic intermediates or energy and the prevention of redox stress. Surprisingly, LDs accumulate under certain conditions such as amino acid starvation. This review explores the biochemical aspects of FA utilization in both physiological contexts and within cancer cells, focusing on the metabolism of TGs, cholesteryl esters (CEs), and mitochondrial FA oxidation. Emphasis is placed on the potential toxicity associated with non-esterified FAs in cytosolic and mitochondrial compartments. Additionally, we discuss mechanisms that lead to increased LD biogenesis due to an inhibited mitochondrial import of FAs.
Keywords: Triglycerides; mitochondrie; mitochondria; Fatty Acids; Oxidation-Reduction; Lipid Metabolism; zvířata; Humans; Lipid Droplets; metabolismus lipidů; triglyceridy; Mitochondria; lipotoxicity; mastné kyseliny; oxidace-redukce; triglycerides; ferroptosis; lipidová tělíska; CPT1; lipid droplets; lidé; Animals